COVID-19: A Review of Potential Treatments (Corticosteroids, Remdesivir, Tocilizumab, Bamlanivimab/Etesevimab, and Casirivimab/Imdevimab) and Pharmacological Considerations. (April 2023) - Nhean, Salin; Varela, Mario E.; Nguyen, Y-Nha; Juarez, Alejandra; Huynh, Tuyen; Udeh, Darlington; Tseng, Alice L.
Objectives : In light of the ongoing global pandemic, this paper reviews data on a number of potential and approved agents for COVID-19 disease management, including corticosteroids, remdesivir, tocilizumab, and monoclonal antibody combinations. Dose considerations, potential drug–drug interactions, and access issues are discussed.Key findings : Remdesivir is the first antiviral agent approved for the treatment of COVID-19, based on results from large clinical trials showing reduction in recovery time, faster clinical improvement, and decrease in time to discharge with remdesivir. Dexamethasone and tocilizumab have demonstrated mortality benefits in large, randomized controlled trials. Consequently, the use of corticosteroids has become the standard of care for hospitalized patients with severe or critical COVID-19, while tocilizumab is recommended for use in combination with a corticosteroid in certain hospitalized patients. Recently, monoclonal antibody combinations bamlanivimab/etesevimab and casirivimab/imdevimab received emergency use authorizations for use in non-hospitalized patients with mild-to-moderate COVID-19 at high risk of disease progression.Summary : As data from large clinical trials emerge, the paradigm of COVID-19 treatments has shifted significantly. The use of corticosteroids, remdesivir, and tocilizumab depend on disease severity. Emerging data on monoclonal antibody combinations are promising, but further data are required. Pharmacists can play a role in ensuring appropriate access, correct administration, and safe use of COVID-19 treatments and are encouraged to stay abreast of new developments.